Quantification of Thyroxine and 3,5,3′-Triiodo-Thyronine in Human and Animal Hearts by a Novel Liquid Chromatography-Tandem Mass Spectrometry Method - Saba, A.; Donzelli, R.; Colligiani, D.; Raffaelli, A.; Nannipieri, M.; Kusmic, C.; Dos Remedios, C. G.; Simonides, W. S.; Iervasi, G.; Zucchi, R. (Hormone and Metabolic Research, 2014)
Assaying tissue T3 and T4 would provide important information in experimental and clinical investigations. A novel method to determine tissue T3 and T4 by HPLC coupled to mass spectrometry is described. The major difference vs. previously described methods lies in the addition of a derivatization step, that is, to convert T3 and T4 into the corresponding butyl esters. The yield of esterification was ̴ 100% for T3 and 80% for T4. The assay was linear (r>0.99) in the range of 0.2–50 ng/ml, accuracy was in the order of 70–75%, and the minimum tissue amount needed was in the order of 50 mg, that is, about one order of magnitude lower than observed with the same equipment (AB Sciex API 4000 triple quadrupole mass spectrometer) if derivatization was omitted. The method allowed detection of T3 and T4 in human left ventricle biopsies yielding concentrations of 1.51±0.16 and 5.94±0.63 pmol/g, respectively. In rats treated with different dosages of exogenous T3 or T4, good correlations (r>0.90) between plasma and myocardial T3 and T4 concentrations were observed, although in specific subsets different plasma T4 concentrations were not associated with different tissue content in T4. We conclude that this method could provide a novel insight into the relationship between plasma and tissue thyroid hormone levels.
Keywords: thyroid hormones; mass spectrometry; heart